2019
DOI: 10.1002/cncr.32396
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcomes among patients with sarcomatoid hepatocellular carcinoma: A population‐based analysis

Abstract: Background Few data are available regarding the management and outcomes among patients with sarcomatoid hepatocellular carcinoma (HCC) due to its rarity. Methods Patients diagnosed with sarcomatoid HCC from 2004 through 2015 were identified in the National Cancer Data Base. Overall survival (OS) was calculated among patients with sarcomatoid versus conventional HCC using a 1:3 propensity score matching based on sex, age, and American Joint Committee on Cancer (AJCC) stage of disease. Results The final analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
45
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 21 publications
10
45
1
Order By: Relevance
“…In this study, we found that regardless of the patients age, the prognosis of patients of TNM stage I-II was signi cantly better than that of patients with stage III-IV. The results were the same as that of a decade-long and population-based Analysis by Lu Wu et al 29 . For patients at the early stage, radical surgery should rstly be considered this may prolong the DFS and help prevent metastasis.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, we found that regardless of the patients age, the prognosis of patients of TNM stage I-II was signi cantly better than that of patients with stage III-IV. The results were the same as that of a decade-long and population-based Analysis by Lu Wu et al 29 . For patients at the early stage, radical surgery should rstly be considered this may prolong the DFS and help prevent metastasis.…”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, in our study, there was no difference in the recurrence pattern between the sarcomatoid and high-grade HCC groups, perhaps due to their similar histological differentiation. Several previous studies have also indicated that the OS of sarcomatoid HCC patients is significantly worse than that of conventional HCC patients, with a 3-year OS rate ranging from 8.0% to 17.5%[ 2 , 8 , 12 , 21 ]. Consistent with previous studies, the current study showed that patients with resected sarcomatoid HCC had an elevated risk of death, with an abysmal 3-year OS compared with the prognosis of resected high-grade HCC patients (17.3% vs 53.4%, P < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…SHC is characterized by a high degree of malignancy, rapid progression, and poor prognosis. The 5-year overall survival (OS) of patients with SHC was found to be worse than that of patients with conventional HCC (5.7% vs 30.1%)[ 5 ]. A lack of specificity is associated with clinical manifestation and etiology of SHC[ 3 ].…”
Section: Discussionmentioning
confidence: 99%